PENGARUH BRAND POSITIONING â€œEVERYDAY IS HOLIDAYâ€ TETHADAP KEPUTUSAN PEMBELIAN PAKET WISATA DI MARGA TOUR BANDUNG (Survei terhadap pengambil keputusan pembelian paket wisata tahun 2011-2013 di Marga Tour Bandung) - Nursilah, Dede; Hendrayati, Heny (Universitas Pendidikan Indonesia, 2015)
The development of tourism in the Bandung become great opportunities for entrepreneurs in the tourism industry including tour and travel business, including Tour Operator. Tour Operator is a company that has activities on planning and organizing the trip for the purpose of tourism (tours). Marga Tour which is under the auspices of PT Marga Indonesia is offering tour packages as its products and services. In the years 2011-2013 the tour packages sales Marga Tour has decline. The solutions fot that problems, the managements of Marga Tour have strategy to put the name Marga Tour in the minds of consumers or in marketing theory called as brand positioning. Through the brand positioning â€œeveryday is holidayâ€, Marga Tour hopes to increase sales of tour packages. The type of this study is descriptive and verificative, the sampling technique that is used is proportionate stratified random sampling. The sample size was calculated with the formula of Slovin and the result is 90 respondents. The data analysis technique used is the technique of path analysis. Based on the results of the statistical test result, the brand positioning â€œeveryday is a holidayâ€ which consists of defining and communicating the competitive frame of reference, points of parity and points of difference has influence towards purchase decisions of tour packages in Marga Tour Bandung, either simultaneously or partially.